Critical remarks about simulation of contract in the Peruvian civil code - Pinto Oliveros, Sheraldine (2016)
Simulation is a complex legal operation in which the parties, with the aim of concealing their real intentions, have made two agreements: one apparent and the other one secret. Although simulation is dealt widely in Civil Law countries, the Civil Code of Peru shows some inconsistencies; especially, to employ a doctrinal classification, which describes different aspects of the fattispecie, as various fattispecie. Therefore, the author develops a critical and comparative analysis about simulation of contract in the Peruvian Civil Code.